Effect of vitamin E and probucol on dietary cholesterol-induced atherosclerosis in rabbits - KARTAL ÖZER, NESRİN; ŞİRİKÇİ, ÖNDER (My University, 1998)
The preventive effect of vitamin E and Probucol against atherosclerosis in rabbits were compared. Atherosclerosis was induced by a 2% cholesterol-containing vitamin E-poor diet (5-10 ppm). Six groups of five rabbits each were studied. Group I (control) was fed on a vitamin E-poor diet. The other groups had the following supplements: group II, 50 mg/kg vitamin E i.m.; group III, 2% cholesterol; group IV, 2% cholesterol plus 50 mg/kg vitamin E i.m., group V, 2% cholesterol plus 1% Probucol; group VI, 2% cholesterol + 1% Probucol plus 50 mg/kg vitamin E i.m. After 4 weeks, aortas were removed and analyzed by light and scanning electron microscopy for atherosclerotic lesions. Samples of the media were analyzed for protein kinase C activity. The aortas of cholesterol-fed rabbits showed typical atherosclerotic lesions, detected by microscopic examination, their media smooth muscle cells exhibited an increase in protein kinase C activity. Vitamin E fully prevented cholesterol-induced atherosclerotic lesions and the induction of protein kinase C activity. Probucol was not effective in preventing either cholesterol-induced atherosclerotic lesions or the induction of protein kinase C activity. These results show that the protective effect of vitamin E against hypercholesterolemic atherosclerosis is not produced by an other antioxidant such as Probucol, and therefore, may not be linked to the antioxidant properties of this vitamin. The effects observed at the level of smooth muscle cells ex vivo suggest an involvement of signal transduction events in the protective effect of vitamin E against atherosclerosis.
Keywords: Animals; Male; Microscopy, Electron, Scanning; Cholesterol; Rabbits; Vitamin E; Endothelium, Vascular; Aorta; Arteriosclerosis; Cholesterol, Dietary; Muscle, Smooth, Vascular; Protein Kinase C; Anticholesteremic Agents; Probucol